The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1017/s0954579420001078
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the accumulation of victimization in vulnerable children: Interpersonal violence among children traumatized by war and disaster in a children's home in Sri Lanka

Abstract: Research in postconflict settings indicated that children's exposure to war and natural disaster is a significant predictor of experiencing violence within their families. However, it is unclear if this effect is driven by characteristics of traumatized children or their parents. To disentangle these different factors we conducted a survey in a children's home in Sri Lanka. A total of 146 institutionalized children (aged 8 to 17) were interviewed using standardized questionnaires administered by local senior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Within these fragile settings, studies have revealed that the burden of IPV against women and child maltreatment is staggering 10–13. War-related violence has long-lasting impacts on the mental health of both adults and children, leading to both higher use of violent discipline as well as maladjustment among children 6 14–17. Indirect experiences of conflict such as increased economic stress are also a shared risk factor for violence and can also lead to increased levels of IPV and child maltreatment within the same household 5…”
Section: Introductionmentioning
confidence: 99%
“…Within these fragile settings, studies have revealed that the burden of IPV against women and child maltreatment is staggering 10–13. War-related violence has long-lasting impacts on the mental health of both adults and children, leading to both higher use of violent discipline as well as maladjustment among children 6 14–17. Indirect experiences of conflict such as increased economic stress are also a shared risk factor for violence and can also lead to increased levels of IPV and child maltreatment within the same household 5…”
Section: Introductionmentioning
confidence: 99%